Clinical efficacy analysis of laparoscopic uterine artery pre-ligation combined with hysteroscopic curettage in the treatment of type II cesarean scar pregnancy - Teng, Dan; Gao, Han; Li, Yanli; Meng, Tingzhu; Shi, Xiuting; Shi, Jie (Frontiers in Medicine, 2023)
Objective: To explore and evaluate the clinical therapeutic effect of laparoscopic uterine artery preligation combined with hysteroscopic curettage in treatment of typeⅡ caesarean scar pregnancy.Methods: This study analyzed the clinical data of 134 patients with type Ⅱ cesarean section in Hubei Provincial Maternal and Child Health Hospital from 2018 to 2022, and 78 patients were included in the final analysis. 37 patients were treated with uterine artery embolization (UAE) combined with hysteroscopic curettage and 41 patients were treated with laparoscopic uterine artery pre-ligation (LUAP) combined with hysteroscopic curettage. We counted the basic information and clinical characteristics of the two groups of patients, then we followed up and compared the short-term and long-term complications .we followed up these patients for 2 years after surgery, then collected and analyzed the compared subsequent pregnancy outcome.Results: We found that there was no significant discrepancies in the success rate of operation, length of hospital stay and intraoperative blood loss between these two different operation modes.Compared with the uterine artery embolization (UAE), the operation cost of laparoscopic uterine artery pre-ligation (LUAP) was particularly lower (p < 0.05). And it was showed that the incidence rate of short-term postoperative complications such as fever and postoperative pelvic pain was lower in patients treated with laparoscopic uterine artery pre-ligation (LUAP) compared with that of uterine artery embolization (UAE). In terms of long-term postoperative complications, the recovery time of menstruation in LUAP group (49.81±11.47) was earlier than that in UAE group (34.90±7.41) (p < 0.05). Decreased menstrual flow in 4.9% of patients in the LUAP group , while 59% patients treated with UAE established that a marked decrease in menstrual flow, and the incidence and severity of intrauterine adhesions was significantly was lower than the UAE group(p < 0.05). Consistent with the aforementioned, the patients treated with LUAP had better postoperative re-pregnancy outcomes in comparison of UAE.Conclusions: LUAP combined with hysteroscopic curettage is a safe and effective surgical scheme for the treatment of typeⅡcesarean scar pregnancies, and it has lower surgical cost, fewer short-term and long-term complications and better postoperative pregnancy outcomes compared with UAE combined with hysteroscopic curettage.